Development of a mathematical model for estimating signal strength at the input of the 802.11 standard receiver - Mykhalevskiy, Dmytro; Vasylkivskyi, Nikolay; Horodetska, Oksana (Eastern-European Journal of Enterprise Technologies, 2017)
A mathematical model of the spatial estimation of signal strength at the input of the receiver for the 802.11 family of standards is proposed, for a central position of the access point in a room. This model allows the assessment of signal level at any point in the room, taking into consideration the maximum possible number of factors of influence. In addition, there is a confidence interval for such a model that makes it possible to estimate the level of signal fluctuations. It was established that the level of signal fluctuations in a room is affected by such basic independent components as the signals, reflected from surfaces in the room, interference obstacles, and noise. In the frequency range of 2.4 GHz for the 802.11 standard, there occurs a rather non-uniform distribution of signals in a room with the creation of amplifying regions, as well as signal weakening, with a difference of up to 10 dbm, and under the most complicated conditions – up to 25 dbm. It was found that the level of signal fluctuations depends on the quantity of simultaneously existing destabilizing factors in the channel for premises where there is a wireless network. Taking these factors into consideration is possible through direct assessment, using the algorithm of monitoring, at a distance of two meters from the radiating antenna of AP. This is the basis for spatial method of signal strength control for any premises in real time